“I Dwell in Possibility”: The Poetics of Space in the Works of 1980s Japanese Avant-Garde Fashion Designers - Vivien Jiaqian Zhu (Comparative Literature: East & West)
What is art? What is history? What is knowledge? What is scholarship? Following the discussion between art and craft, I reflect on the use of textile with scholarship from Julia Bryan-Wilson and Winnie Wong. Inspired by Susan Foster’s article “Choreography Empathy,” and Georgina Kleege’s More Than Meets the Eye, I associate space with choreography and kinesthetic movement – particularly the concept of “ma 間” for the 1960s-1980s Japanese fashion designers.